BIOMARCADORES ASSOCIADOS A GRAVIDADE NA INFECÇÃO POR SARS-CoV-2 - Fabiani de Morais Batista (2023)
Coronavirus disease 2019 (COVID-19) is highly infectious. Studies have documented the relationship between COVID-19 severity and circulating levels of C-reactive protein (CRP), interleukin-6 (IL-6) and D-dimer. In patients with severe COVID-19, elevated levels of IL-6 and interleukin 2 (IL-2) and tumor necrosis factor-Alpha (TNF-α) have been found. Other markers are similarly identified when critically ill COVID-19 patients had higher circulating levels of IL-2, IL-7, IL-10, and TNF-α. A better understanding of immune responses to SARS-CoV-2 infection that differentiate cases from levels of severity is critical for an accurate assessment of prognosis and identification of future biomarkers. The aim of the study was to identify differences in serological biomarker levels between individuals with mild and severe COVID-19. Methods: Participants from four Brazilian cities, aged over 18 years, were included from October 2020 to June 2021. Participants were tested for the presence of SARS-CoV-2 through Polymerase Chain Reaction with Quantitative Reverse Editing (RT-qPCR) and additionally had a blood sample collected for further analysis of biomarkers. Participants were divided into index cases (participants with clinical suspicion of flu, with up to 11 days of symptoms, with a positive test for SARS-CoV-2, hospitalized or not) and household contacts of non-hospitalized index cases (regardless of whether or not they had symptoms), which made it possible to analyze the selection of asymptomatic positive participants and a negative control group. Analysis of serological biomarkers was performed using MAGPIX Luminex® xMAP® technology, using three different MILLIPLEX® Map panels. Seventy-one biomarkers were quantified from participants with SARS-CoV-2 infection and control group. We correlated the levels of biological markers with negative control (C), asymptomatic (A), non-hospitalized (mild-M) and hospitalized (severe-S) groups. Results: 48 participants were included, most of them female (67%), with a median age of 47 years. Among angiogenesis biomarkers, we identified 6/17 (EGF, IL-8, HGF, HB-EGF, VEGF-C, VEGF-A) that showed significantly elevated levels in severe cases. Among cardiovascular disease biomarkers, 7/10 showed significant differences between groups (D-dimer, GDF-15, myoglobin, sICAM-1, MPO, P-selectin and Lipocalinlipocalin-2/NGAL). The D-dimer biomarkers, GDF-15 and sICAM-1 had the highest levels in severe cases when compared to the other groups. Of the cytokine/chemokine evaluations, 9/44 showed a statistically significant difference between groups (IL-6, IL-7, IL-18, IP-10, M-CSF, MDC, MIP-1 beta, PDGF-AA and TNF alpha). IL-6, IP-10, M-CSF, MDC and MIP-1 beta were higher in severe cases than in group C. Conclusion: This is the first compressive study in Brazil that identified and described levels of biological markers related to levels of cytokines, cardiac and endothelial system. It can be seen that most of the changes in biomarkers, when compared between the groups, showed a statistically significant difference. Although it was possible to find changes in most biomarkers in hospitalized participants, additional studies are motivated to improve the association with clinical evolution, monitoring and risk factors of individuals with COVID-19.